2018
DOI: 10.4314/ijbcs.v12i2.6
|View full text |Cite
|
Sign up to set email alerts
|

A primal incrimination of<i> Cedecea davisae</i> with post-prostatectomy urinary tract infection in Nigeria

Abstract: Cedecea species are recent members of the family Enterobacteriaceae and are rarely incriminated in human infections. A patient with protracted urinary tract infection, post-prostatectomy, was referred to Lahor Research Laboratories, Benin City, Nigeria for routine culture and susceptibility testing. Three consecutive mid-stream urine samples from him yielded pure, heavy, growths of an apparently same Gram negative, nonspore forming, non-capsulated, motile, rod-shaped bacterium, which was lipase, citrate, methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…The distribution of etiologic agents of surgical wound infections showed that P. aeruginosa (62.6%) was found to be more predominant. This is in conformity with the study of Agbonlahor et al (2018) who also found that P. aeruginosa were more prevalent in surgical wound infections [38]. Thirty-four (54.8%) strains were found to be multidrug resistant Pseudomonas aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The distribution of etiologic agents of surgical wound infections showed that P. aeruginosa (62.6%) was found to be more predominant. This is in conformity with the study of Agbonlahor et al (2018) who also found that P. aeruginosa were more prevalent in surgical wound infections [38]. Thirty-four (54.8%) strains were found to be multidrug resistant Pseudomonas aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 92%
“…[40] reported that bacterial isolated from surgical wound infections are mostly resistant to Ceftazidime and Augmentin. This is most likely to be due to the presence of enzymes such as Cephalosporinase and Penicillinase which can prevent the activity of Beta-lactam ring of the antibiotics [38]. Current problems linked with the use of antibiotics, increased prevalence of multiple drug resistant (MDR) strains of a number of pathogenic bacteria has revitalized the interest in plants with antimicrobial properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…Amplification and sequencing were done as described by Agbonlahor et al ( 21 ), with the following modifications: Purification was done with the Applied Biosystems Incorporation (ABI) V3.1 Big dye kit according to manufacturer’s instructions. The labeled products were then cleaned with the Zymo Seq clean-up kit (USA) in accordance with manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The ultra-pure DNA was sequenced with ABI3500XL analyser at Functional Bioscience, Madison, USA. Sequences data generated were analysed with Geneious version 9.0.5 and phylogenetic tree were constructed using neighbour-joining method as described by Agbonlahor et al ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of AmpC production and porin deficiency in the cell wall contributes to its multidrug resistance [2]. It possesses plasmid carrying multidrug resistance genes, through which it can transfer its genetic materials to other susceptible bacteria in the same ecosystem [3]. To the best of our knowledge, only 12 cases of C. davisae bacteremia have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%